2014
DOI: 10.1042/cs20140344
|View full text |Cite
|
Sign up to set email alerts
|

Anaemia in chronic obstructive pulmonary disease: an insight into its prevalence and pathophysiology

Abstract: Chronic obstructive pulmonary disease (COPD) is a major health problem, with increasing morbidity and mortality. There is a growing literature regarding the extra-pulmonary manifestations of COPD, which can have a significant impact on symptom burden and disease progression. Anaemia is one of the more recently identified co-morbidities, with a prevalence that varies between 4.9% and 38% depending on patient characteristics and the diagnostic criteria used. Systemic inflammation seems to be an important factor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
20
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 131 publications
(151 reference statements)
4
20
0
1
Order By: Relevance
“…If the patient was known to suffer from diabetes, chronic lung disease, or heart failure, and no other underlying cause of ACD could be established, these diseases were assigned as the underlying cause of ACD. [7][8][9][10][11][12][13] Any prescription of oral iron supplementation, as well as the time (in weeks) from the confirmation of ACD to the establishment of the underlying cause were also recorded.…”
Section: Data Collectionmentioning
confidence: 99%
See 1 more Smart Citation
“…If the patient was known to suffer from diabetes, chronic lung disease, or heart failure, and no other underlying cause of ACD could be established, these diseases were assigned as the underlying cause of ACD. [7][8][9][10][11][12][13] Any prescription of oral iron supplementation, as well as the time (in weeks) from the confirmation of ACD to the establishment of the underlying cause were also recorded.…”
Section: Data Collectionmentioning
confidence: 99%
“…[3][4][5][6] This type of anaemia can be caused by a variety of conditions, including acute and chronic infections, chronic diseases, autoimmune disorders, acute trauma, surgical interventions, renal failure, heart failure, and malignancies. [7][8][9][10][11][12][13] ACD is described as a functional iron deficiency caused by elevated hepcidin levels, which implies that oral iron supplementation is unnecessary. [14][15][16] Patients with ACD aged 50 years have a relative risk for mortality of 1.48 compared to adults without anaemia.…”
Section: Introductionmentioning
confidence: 99%
“…Anemia may develop in response to chronic disease, inflammation, iron and vitamin deficiencies, comorbidities, or hypogonadism, or anemia may be treatment related. The literature indicates that anemia resulting either from chronic disease or inflammation is predominant in COPD . Therefore, we propose that anemia is a better predictor of outcomes than acidaemia in AECOPD patients requiring IMV.…”
Section: Discussionmentioning
confidence: 99%
“…First, systemic inflammation is a key pathophysiologic element of COPD, resulting in enhanced retention of iron within the cells of reticuloendothelial system. 7 During acute COPD exacerbations, repeated bursts of inflammation lead to a further distortion on iron homeostasis, resulting to its diversion from the circulation. Increased levels of inflammatory cytokines and disorders in the synthesis, release and activity of hepcidin, a peptide hormone that regulates iron homeostasis, both play a significant role in this phenomenon.…”
mentioning
confidence: 99%
“…As iron becomes unavailable for utilization, patients develop a functional iron deficiency, with or without anaemia. 7 Second, congestive heart failure and pulmonary hypertension, which are common co-morbidities among COPD patients, are frequently complicated by NAID. Finally, iron deficiency might also be an absolute one; even though data on mineral intake among COPD patients are limited, a small study found that daily iron intake among COPD patients was about half that among age-matched controls, 8 which could further contribute to a pre-existing functional iron deficiency.…”
mentioning
confidence: 99%